Study on Micro Displacement Mechanism of Hydraulic Fracturing by Oil Displacement Agent at High Pressure. (23rd July 2021) - Wang, Fengjiao; Wang, Xu; Liu, Yikun; Deng, Qingjun; Hu, Jianan; Lv, Yingbo
Abstract : The type-III oil formations in Daqing Oilfield are the representatives of medium-low permeability reservoirs in ultrahigh water cut oilfields of China, which is characterized by bad connectivity of pores and throats, dispersed residual oil distribution, and difficult to displace effectively. In order to produce the residual oil, we propose a new EOR (enhanced oil recovery) method which is hydraulic fracturing by an oil displacement agent at high pressure. In this paper, firstly, we have performed three sets of displacement experiments under different conditions to provide the basis for the analysis of changes in core pore structure and wettability. Next, overburden pressure porosity and permeability tests were used to analyze the effect of the injection of an oil displacement agent at high pressure on core physical properties. Correspondingly, the constant speed mercury injection tests were used to determine the radius distribution of pore throat and change of seepage resistance under different displacement conditions. Moreover, the scanning electron microscopy (SEM) tests of cores were carried out to observe and analyze changes in pore-throat size and connectivity, mineral particle accumulation, and cementation before and after hydraulic fracturing by an oil displacement agent at high pressure. Finally, core wettability tests were conducted to discuss and analyze the rule of core wettability change in hydraulic fracturing by an oil displacement agent at high pressure, and its mechanism of wettability changes. Research shows that increasing the formation energy is the most important mechanism of EOR by a fracturing-seepage-displacement method. Additionally, the type of an oil displacement agent has less effect. After an oil displacement agent at high pressure is injected to fracture the formation, it not only provides efficient flow channel and larger sweep volume for an oil displacement agent. Under the flushing action of high-pressure injection fluid, the original way of line or point contact between mineral particles gradually changes to free particles. Therefore, the pore throat size increases, some larger pores are formed, and the overall flow resistance decreases. After the injection of fluid at high pressure, the energy in formation has increased and the core wettability changes from oil-wet to weakly water-wet. This is not only because the residual oil on the pore surface is flushed by high pressure; in addition, the adsorption of an oil displacement agent on the rock surface reduces the liquid-solid interface energy and changes the wettability, thus improving the oil displacement efficiency.